The emergence of the Omicron XBB.1.5 variant in India: a brief report on clinical presentation of a few cases - Samal, Jasmine; Bhugra, Arjun; Suroliya, Varun; Gautam, Pramod; Agarwal, Reshu; Bihari, Chhagan; Gupta, Ekta (Frontiers in Virology, 2023)
Three years navigating in the COVID-19 pandemic, the constant evolution of novel variants/subvariants is keeping our scientists on toes. Seeing the last few months, a global plummet in COVID-19 cases made us believe that we are transitioning towards endemic COVID-19. However, the new omicron offshoots (XBB variants) are driving new surge of cases around the world. A few preliminary research findings suggest that XBB.1.5 subvariant is more immune-evasive and displays higher binding to ACE2 human receptor than its other related omicron subvariants in circulation. In this first of its kind report, we discuss a few XBB.1.5 cases and its clinical characteristics reported in Delhi State, North India.